Native American Survivance and the Representation of Native American Literary Resistance: A Postmodern Reading Gerald Vizenor’s Bearheart: The Heirship Chronicles (1990) as a Case Study - Guettaf ,Mihoub; Kourdourli, Abdelkader (Faculty of Letters and Foreign Languages Department of English, 2023)
With Gerald Vizenor's invention of survivance, Native American literary resistance takes another shift. Many writers have embraced survivance; however, the concept still needs to improve in identifying its elements. This study aims to identify and highlight some of the elements of survivance. Additionally, it explains each element (storytelling, myths, tricksters, and religion) in the light of Vizenor's novel Bearheart. Moreover, it discusses the trickster as a postmodern linguistic technique. This study adopts an analytical approach because it is suitable for analysing the setting, context, and characters. After the analysis and discussion of the novel, it appears that Vizenor uses storytelling, myths, tricksters, and religion as elements of survivance